Meta-Analysis of the Outcome After Postcardiotomy Venoarterial Extracorporeal Membrane Oxygenation in Adult Patients - Biancari F; Perrotti A; Dalén M; Guerrieri M; Fiore A; Reichart D; Dell'Aquila AM; Gatti G; Ala-Kokko T; Kinnunen EM; Tauriainen T; Chocron S; et al. (United States, 2025)
Objective
This study was planned to pool existing data on outcome and to evaluate the efficacy of postcardiotomy venoarterial extracorporeal membrane oxygenation (VA-ECMO) in adult patients.
Design
Systematic review of the literature and meta-analysis.
Setting
Multi-institutional study.
Participants
Adult patients with acute heart failure immediately after cardiac surgery.
Interventions
VA-ECMO after cardiac surgery. Studies evaluating only heart transplant patients were excluded from this analysis.
Measurements and Main Results
A literature search was performed to identify studies published since 2000. Thirty-one studies reported on 2,986 patients (mean age, 58.1 years) who required postcardiotomy VA-ECMO. The weaning rate from VA-ECMO was 59.5% and hospital survival was 36.1% (95% CI 31.5-40.8). The pooled rate of reoperation for bleeding was 42.9%, major neurological event 11.3%, lower limb ischemia 10.8%, deep sternal wound infection/mediastinitis 14.7%, and renal replacement therapy 47.1%. The pooled mean number of transfused red blood cell units was 17.7 (95% CI 13.3-22.1). The mean stay in the intensive care unit was 13.3 days (95% CI 10.2-16.4). Survivors were significantly younger (mean, 55.7 v 63.6 years, p = 0.015) and their blood lactate level before starting VA-ECMO was lower (mean, 7.7 v 10.7 mmol/L, p = 0.028) than patients who died. One-year survival rate was 30.9% (95% CI 24.3-37.5).
Conclusions
Pooled data showed that VA-ECMO may salvage one-third of patients unresponsive to any other resuscitative treatment after adult cardiac surgery.